Utilization Practices of Ancient Manuscript Collections by Students of the Islamic Cultural History Study Program at UIN Ar-Raniry in the Aceh Museum Library - Nong Fatina Sari; Nurdin AR; Nurul Rahmi; Nugroho Arief Setiawan (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background: Ancient manuscripts are cultural heritage that contain various important information about history, religion, customs, and knowledge of the past. The collection of ancient manuscripts stored at the Aceh Museum holds immense value, both as a source of learning and research. However, the effectiveness and depth of their utilization by students remain questionable. Objectives: This study aims to determine how students of the Islamic Cultural History Program at UIN Ar-Raniry Banda Aceh utilize ancient manuscripts at the Aceh Museum, as well as to identify the factors that influence, the challenges faced, and the forms of utilization carried out. Methods: The study employs a qualitative approach using a descriptive method. Participants include 15 students and 5 museum staff members from the Aceh Museum, selected through simple random sampling. Data was collected through observation, semi-structured interviews, and documentation, and analyzed qualitatively through the stages of data collection, data reduction, data presentation, and conclusion drawing. Result: The results of the study indicate that students utilize ancient manuscripts primarily in an academic context to fulfill assignments for courses in Philology and Ancient Manuscript Studies. Internal factors influencing utilization include academic needs, interest, and motivation, while external factors include the completeness of the collection, librarian services, and faculty support. The main challenges faced by students are limited ability to read ancient scripts and the scarcity of available transliterations. Conclusion: The utilization of ancient manuscripts by students is already underway but remains limited to practical academic purposes. To optimize their use, additional strategies are needed, including literacy training, digitization of collections, and the integration of manuscript-based learning to enable deeper and more sustainable utilization of ancient manuscripts.